The role of integration between the earned value management model and the value flow map in rationalizing the costs of construction projects: applied research in Al-Rasheed General Company for Construction Contracting (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research problem is that most of the construction projects exceed the planned value, due to the failure to implement the plans on time. The current study aims to monitor the implementation of the project and for each of the executed tasks of the table of quantities in order to detect deviations at the time they occur, evaluate the time and cost performance, and then identify the areas of waste and analyze the implementation of each task in order to diagnose the underlying problems and find possible and applicable solutions in the environment Iraqi. The research was applied in one of the companies specialized in the field of construction projects, and one of the most important conclusions reached is the possibility of applying the Earned value management model to the tasks executed during the work stages, as well as the possibility of applying a value stream map to construction projects to rationalize their costs.